Conservative Treatment of a Radicular Cyst Associated witha Primary Mandibular Molar - Hoseain Afshar; Zahra Baniameri (Islamic Dental Association of Iran, 2015)
Introduction: Radicular cysts (RCs) are the most common odontogenic cystic lesions with an inflammatory origin. Radicular cysts originate from epithelial remnants of the periodontal ligament as a result of inflammation,which is generally a consequence of pulp necrosis. Dental caries is the most common etiology of RCs and theyaremost commonlyreported in primary mandibular molars. Treatment options include root canal therapy, extraction and surgery. Case Presentation: A 10.5 year-old patient presented to the Pediatric Dentistry Department of Tehran University of Medical Sciences (TUMS) with a RC associated with a primary mandibular second molar. We performed non-surgical conservative treatment by extracting the involved tooth. After two years of follow up, the lesion healed and the second premolar erupted.